Raman spectroscopy studies of multipotent stromal cells differentiation for bone engineering application - Ponzoni, Raquel de Almeida Rocha (2017)
Raman spectroscopy (RS) is a label-free method based in the inelastic scattering of laser-light and can be used non-destructively to provide a biomolecular fingerprint of cells. Mesenchymal stromal cells (MSCs) are known for their heterogeneity and, unlike other stem cells, lack a unique marker, thus compromising their application in regenerative medicine. In this work, RS was investigated for its capacity to discriminate MSCs subpopulations, whilst still providing markers of their function. Four immortalised clonal MSC lines, which express the same surface proteins, have contrasting differentiation capacities and were not totally discriminated by global gene expression analyses, were investigated. Air-dried and live cell experiments were performed, as well as the induction of one cell line into ostegenesis and adipogenesis. Relative differences between proteins and DNA/RNA provided the discrimination of the undifferentiated MSCs towards their differentiation competence. Raman spectroscopy also showed clear progression of the adipogenic differentiation. During osteogenesis, the MSCs formed mineralised nodules with an architecture similar to native human bone. The RS investigation of these MSCs showed that the obtained Raman markers could be used to predict differentiation competence in undifferentiated cells and then, followed throughout osteogenesis.